Respuesta :

Space

Answer:

No solution.

Step-by-step explanation:

Step 1: Write inequality

3(x - 2) + 1 ≥ x + 2(x + 2)

Step 2: Solve for x

  1. Distribute: 3x - 6 + 1 ≥ x + 2x + 4
  2. Combine like terms: 3x - 5 ≥ 3x + 4
  3. Add 5 to both sides: 3x ≥ 3x + 9
  4. Subtract 3x on both sides: 0 ≥ 9

Here we see that the statement is false. Therefore, you cannot solve for the inequality.

Answer:

Your answer is: No solution

Step-by-step explanation:

There are no values of  x  that make the inequality true.

Hope this helped : )